Biallelic losses of 13q do not confer a poorer outcome in chronic lymphocytic leukaemia: analysis of 627 patients with isolated 13q deletion. (19th July 2013) - Puiggros, Anna; Delgado, Julio; Rodriguez‐Vicente, Ana; Collado, Rosa; Aventín, Anna; Luño, Elisa; Grau, Javier; Hernandez, José Ángel; Marugán, Isabel; Ardanaz, Maite; González, Teresa; Valiente, Alberto; et al.
Summary: Losses in 13q as a sole abnormality confer a good prognosis in chronic lymphocytic leukaemia (CLL). Nevertheless, its heterogeneity has been demonstrated and the clinical significance of biallelic 13q deletions remains controversial. We compared the clinico‐biological characteristics of a series of 627 patients harbouring isolated 13q deletions by fluorescence in situ hybridization (FISH), either monoallelic (13q × 1), biallelic (13q × 2), or the coexistence of both clones (13qM). The most frequent 13q deletion was 13q × 1 (82·1%), while 13q × 2 and 13qM represented 8·6% and 9·3% of patients respectively. The median percentage of altered nuclei significantly differed across groups: 55%, 72·5% and 80% in 13q × 1, 13q × 2 and 13qM ( P < 0·001). However, no significant differences in the clinical outcome among 13q groups were found. From 84 patients with sequential FISH studies, eight patients lost the remaining allele of 13q whereas none of them changed from 13q × 2 to the 13q × 1 group. The percentage of abnormal cells detected by FISH had a significant impact on the five‐year cumulative incidence of treatment and the overall survival, 90% being the highest predictive power cut‐off. In conclusion, loss of the remaining 13q allele is not enough to entail a worse prognosis in CLL. The presence of isolated 13q deletion can be risk‐stratified according to the percentage of altered cells.